Компьютерный прибор для измерения динамических параметров сердечно-сосудистой системы - Чернецкий, В.В.; Брайко, Ю.А.; Имамутдинова, Р.Г. (Комп’ютерні засоби, мережі та системи, 2014)
Computer device realized phonen-doscop method of the measuring the blood pressure on the vessel is offered.